Experimental Investigation of Air–Fuel Mixing Effects on Flame Characteristics in a Direct fired Burner - Cheolwoo Lee; Insu Kim; Junggoo Hong (Energies, 2021)
The length and pattern of air–fuel mixing plays a significant role in the uniformity, flame temperature, and emission characteristics, which can lead to a superior product quality in a non-oxidizing direct fired burner for a cold-rolled steel plate furnace. In this study, a diffusion-flame-type burner and partially-premixed-type burner were experimentally investigated to understand their effects on flame shape, flame temperature, and exhaust gas characteristics. With this aim, fuel nozzle size, nozzle hole number, fuel injection angle, and mixing distance of fuel and air were varied during the experiments. Computational fluid dynamics simulations were also performed to investigate the air–fuel mixing state for a nozzle-mixed burner and a partially-premixed burner. The results show that the flame temperature of the partially-premixed burner increases by up to 26 °C on average compared to that of the nozzle-mixed burner. It is also shown that the mixing distance plays an important role in the flame temperature of the partially-premixed burner. In addition, the residual oxygen concentration and volume ratio of CO/CO2 in the flue gas of the partially-premixed burner exhibit lower concentrations compared to those of the diffusion flame burner.